2021
DOI: 10.1183/13993003.01470-2021
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical ventilation promotes lung tumour spread by modulation of cholesterol cell content

Abstract: Mechanical stretch of cancer cells can alter their invasiveness. During mechanical ventilation, lungs may be exposed to an increased amount of stretch, but the consequences on lung tumors have not been explored. To characterize the influence of mechanical ventilation on the behavior of lung tumors, invasiveness assays and transcriptomic analyses were performed in cancer cell lines cultured in static conditions or under cyclic stretch. Mice harbouring lung melanoma implants were submitted to mechanical ventilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Current studies also highlight the potential of curcumin in inhibiting PCSK9's effect on cutaneous melanoma by regulating oxidative stress-related signaling pathways [33]. PCSK9's involvement in the development and metastasis of lung and liver melanomas, through LDLR or other mechanisms [34,35], underscores the potential of PCSK9 inhibitors in reducing melanoma risk and improving prognosis.…”
Section: Discussionmentioning
confidence: 95%
“…Current studies also highlight the potential of curcumin in inhibiting PCSK9's effect on cutaneous melanoma by regulating oxidative stress-related signaling pathways [33]. PCSK9's involvement in the development and metastasis of lung and liver melanomas, through LDLR or other mechanisms [34,35], underscores the potential of PCSK9 inhibitors in reducing melanoma risk and improving prognosis.…”
Section: Discussionmentioning
confidence: 95%
“… 334 , 350 , 351 Elevated PCSK9 expression has also been reported to be instrumental in promoting the metastasis and invasiveness of lung cancer and melanoma (specifically within the lung). 352 , 353 In addition, a clinical cohort study involving 44 elderly patients with non-small-cell lung cancer (NSCLC), who were treated with the ICI, nivolumab, revealed that NSCLC patients with lower levels of blood PCSK9 ( < 95 ng/mL) enjoyed a significantly prolonged OS during the second therapeutic cycle. 354 These findings were reinforced in a recent report where advanced NSCLC patients exhibiting low baseline plasma PCSK9 levels gained the most benefit from ICI therapy.…”
Section: The Role Of Pcsk9 In Various Disordersmentioning
confidence: 99%
“… 344 Moreover, a PCSK9-enriched microenvironment induced by either mechanical ventilation or Ahnak could significantly facilitate melanoma cells to metastasize into the lung in mouse B16F10 melanoma models, which could be rescued by genetic deletion of PCSK9 or an anti-PCSK9 mAb. 352 , 353 Hence, targeting PCSK9 may be a robust and novel strategy to effectively restrict invasion and metastasis in various cancers. (Fig.…”
Section: The Role Of Pcsk9 In Various Disordersmentioning
confidence: 99%
“…Cholesterol is an essential component of cell membranes that plays a wide range of physiological roles in the body [ 10 ]. Furthermore, changes in the cholesterol content of the cell membrane directly influence tumor cell stiffness [ 11 ]. The physical properties exhibited on the surface of target cells can potentially influence the dynamic interactions between tumor and T cells [ 12 ].…”
mentioning
confidence: 99%